Domestic Enemies Servants and Their Masters in Old Regime France - Fairchilds, Cissie (Johns Hopkins University Press, 2019)
Originally published in 1983. This book cuts across the class boundaries of traditionally separate fields of social history. It investigates the social origins of servants, their incomes, their marriage and family patterns, their career patterns, their possibilities for social mobility, their political activities, and their criminality. But it also investigates the history of the family and domestic life in France in the sixteenth, seventeenth, and eighteenth centuries, for servants were, at least until the rise of the affectionate nuclear family in the middle of the eighteenth century, considered part of the families of those they served. Finally, this book is also an essay on the history of social relationships in the ancien régime, not only those between masters and servants but also the broader relationships between the ruling elite and the lower classes. The introduction gives basic facts about the composition of households during the Old Regime and explores the attitudes and assumptions that underlay the employment of servants. It also shows how both these attitudes and the households themselves changed dramatically in the last decades before the French Revolution. Part 1 is devoted to the servants themselves. One chapter deals with their lives within their employers' households: their work, their living conditions, their socializing and leisure-time activities. A second examines their private lives: their social origins, marriage and family patterns, their moneymaking and their criminality. And a third explores their relationships with and attitudes toward their masters. In part 2, the focus shifts to an examination of master-servant relationships from the masters' point of view. The first chapter deals with master-servant relationships in general by discussing the factors that determined how employers treated their domestics. The second and third chapters explore two special relationships: masters' sexual relationships with their servants and their relationships with the servants who cared for them in childhood. The epilogue traces the impact of the French Revolution on domestic service and sketches some of the changes in the household that were to come in the nineteenth century.